Wujud Smart Governance di Indonesia: Partisipasi Masyarakat dan Efektivitas Penggunaan Aplikasi SALAMAN dalam Pelayanan Administrasi Kependudukan di Kota Bandung - Nurlita, Dwie Shinta; Addinari, Shabina Sundus; Herlambang, Syaira Diasyifa; Darmawan, Ivan (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2024)
One of the innovations in the implementation of e-government and Smart Government in Bandung City is the launch of the Salaman application created by the Bandung City Population and Civil Registry Office. This innovation aims to facilitate the public in population administration services. The method used in this article is descriptive analytical and literature review. The research is intended to collect information on the status of existing symptoms. This research is intended to determine the level of effectiveness, community participation, and the impacts that occur in the implementation of the Salaman application innovation by the Bandung City Population and Civil Registry Office. The results of the study indicate that population administration services through the Salaman application run effectively and some people feel satisfied and helped by the innovation, although in its implementation there are still obstacles, for example people who do not understand and still have difficulty understanding and accessing various applications provided by the government and end up getting conventional services. Innovation, Salaman Application, e-government, service